Constraining Exoplanet Metallicities and Aerosols with the Contribution to ARIEL Spectroscopy of Exoplanets (CASE). (20th August 2019) - Zellem, Robert T.; Swain, Mark R.; Cowan, Nicolas B.; Bryden, Geoffrey; Komacek, Thaddeus D.; Colavita, Mark; Ardila, David; Roudier, Gael M.; Fortney, Jonathan J.; Bean, Jacob; Line, Michael R.; Griffith, Caitlin A.; et al.
Abstract: Launching in 2028, ESA's 0.64 m 2 Atmospheric Remote-sensing Exoplanet Large-survey (ARIEL) survey of ∼1000 transiting exoplanets will build on the legacies of NASA's Kepler and Transiting Exoplanet Survey Satellite ( TESS ), and complement the James Webb Space Telescope ( JWST ) by placing its high-precision exoplanet observations into a large, statistically significant planetary population context. With continuous 0.5–7.8 μ m coverage from both FGS (0.5–0.6, 0.6–0.81, and 0.81–1.1 μ m photometry; 1.1–1.95 μ m spectroscopy) and AIRS (1.95–7.80 μ m spectroscopy), ARIEL will determine atmospheric compositions and probe planetary formation histories during its 3.5 yr mission. NASA's proposed Contribution to ARIEL Spectroscopy of Exoplanets (CASE) would be a subsystem of ARIEL's Fine Guidance Sensor (FGS) instrument consisting of two visible-to-infrared detectors, associated readout electronics, and thermal control hardware. FGS, to be built by the Polish Academy of Sciences Space Research Centre, will provide both fine guiding and visible to near-infrared photometry and spectroscopy, providing powerful diagnostics of atmospheric aerosol contribution and planetary albedo, which play a crucial role in establishing planetary energy balance. The CASE team presents here an independent study of the capabilities of ARIEL to measure exoplanetary metallicities, which probe the conditions of planet formation, and FGS to measure scattering spectral slopes, which indicate if an exoplanet has atmospheric aerosols (clouds and hazes), and geometric albedos, which help establish planetary climate. Our simulations assume that ARIEL's performance will be 1.3× the photon-noise limit. This value is motivated by current transiting exoplanet observations: Spitzer /IRAC and Hubble /WFC3 have empirically achieved 1.15× the photon-noise limit. One could expect similar performance from ARIEL, JWST, and other proposed future missions such as HabEx, LUVOIR, and Origins. Our design reference mission simulations show that ARIEL could measure the mass–metallicity relationship of its 1000-planet single-visit sample to >7.5 σ and that FGS could distinguish between clear, cloudy, and hazy skies and constrain an exoplanet's atmospheric aerosol composition to ≳5 σ for hundreds of targets, providing statistically transformative science for exoplanet atmospheres.